Atrioventricular block after ASD closure. Issue 2 (1st August 2016) - Asakai, Hiroko; Weskamp, Sofia; Eastaugh, Lucas; d'Udekem, Yves; Pflaumer, Andreas
Abstract : Objective: Secundum atrial septal defect (ASD) is a common congenital heart defect. There is limited data on both early and late atrioventricular (AV) block post ASD closure. The aim of this study was to determine the incidence and risk factors of AV block associated with ASD closure. Methods: A retrospective analysis of all patients who underwent ASD closure either with a device or surgical method at the Royal Children's Hospital Melbourne between 1996 and 2010 was performed. Baseline demographics, procedural details and follow-up data were collected from medical records. Results: A total of 378 patients were identified; 242 in the device group and 136 in the surgical group. Fourteen patients (3.7%) had AV block (1 with second degree and 13 with first degree) at a median follow-up of 28 months; 11/242 (4.5%) in the device group and 3/135 (2.2%) in the surgical group (p=0.39). Six patients had new-onset AV block after ASD closure. In the device subgroup, patients with AV block at follow-up had a larger indexed device size compared with those without (22 (15–31) vs 18(7–38), p=0.02). Multivariate analysis revealed the presence of AV block either pre procedure or post procedure to be the only variables associated with late AV block. Conclusions: Late AV block in patients with repaired ASD is rare and most likely independent of the technique used. In the device subgroup, the only risk factor identified to be associated with late AV block was the presence of either preprocedural or postprocedural AV block, so long-term follow-up for these patients should be provided.